A Note on "Continuous Invertibility and Stable QML Estimation of the EGARCH(1,1) Model" - Francisco Blasques; Paolo Gorgi; Siem Jan Koopman; Olivier Wintenberger (Tinbergen Institute, 2015)
We revisit Wintenberger (2013) on the continuous invertibility of the EGARCH(1,1) model. We note that the definition of continuous invertibility adopted in Wintenberger (2013) may not always be sufficient to deliver strong consistency of the QMLE. We also take the opportunity to provide other small clarifications and additions.
Keywords: C01; C22; C51; 330; invertibility; quasi-maximum likelihood estimator; volatility models